ENST00000534735 inhibits proliferation and migration, promotes apoptosis and pyroptosis of endometrial cancer via OSBPL3 through APMK/SIRT1/NF-κB pathway - Shuzhi Shan; Xiao Wang; Lijie Qian; Chunxiao Wang; Sufen Zhao (Heliyon, 2024)
Background: The complete understanding of the biological roles of long non-coding RNAs (lncRNAs) in cancer remains elusive. The findings of this study indicate that the newly discovered lncRNA ENST00000534735 exhibited a decreased expression in both endometrial cancer (EC) tissues and cell lines. Methods: The expression of ENST00000534735 in EC tissues was detected using RNA-sequencing analysis. The effects of ENST00000534735 on cell proliferation, migration, apoptosis, and pyroptosis were determined via in vitro and in vivo experiments. The proteins that interact with ENST00000534735 were confirmed by RNA pull-down assay. Furthermore, an investigation was conducted on the impact of ENST00000534735 on the in vivo growth of EC through a tumorigenicity assay in nude mice. Results: We found that ENST00000534735 was significantly down-regulated in EC tissues compared to their adjacent non-cancerous tissues. The ectopic expression of ENST00000534735 drastically inhibited lung cancer cell proliferation and migration ability and facilitated apoptosis and pyroptosis. Knockdown of ENST00000534735 increased OSBPL3 expression, and the tumor-suppressing effects of ENST00000534735 overexpression were reversed by upregulation of OSBPL3 via the APMK/SIRT1/NF-κB pathway. The in vivo tumorigenic assays conducted on nude mice revealed that the excessive expression of ENST00000534735 impeded the growth of EC. Conclusions: All results elucidated the role and molecular mechanism of ENST00000534735 in the malignant development of EC. ENST00000534735, a new antioncogene in EC, may serve as a survival biomarker or therapeutic target for EC.